Tail biting and production performance in fattening pigs - Sinisalo, Alina; Niemi, Jarkko K.; Heinonen, Mari; Valros, Anna (Elsevier, 2012)
Tail biting is an important animal welfare problem that is known to negatively affect production performance. We studied how tail biting influences the production performance in fattening pigs. Production performance was measured as the average daily gain (ADG), gross feed conversion ratio (FCR), red meat percentage (Meat%). Pigs' genetic merit, gender and breed were taken into account in the analysis. In addition, differences between breeds and genders in the prevalence of tail biting were studied. The data were collected from a farm and they included individual records for 3190 pigs. Altogether, 11.4% pigs were identified as victims. Between boars, females and barrows there were not significant differences in the risk for being a tail biting victim. Yorkshire (Y) pigs were identified as victims more often than Landrace (L) pigs, 13.8% and 10.0%, respectively (p=0.001). Non-victims had a greater ADG than victims (33.4 g/d difference in observed means but 10.8 g/d difference when adjusted to genetic merit). These values correspond to 1 to 3% reduction in ADG. By contrast, no significant differences between victims' and non-victims' FCR and Meat% were found. The results highlight the need to take into account genetics, breed and other factors affecting production performance when estimating the effects of a health disorder.
Keywords: Ma; hännänpurenta; sika; sikarodut; tuottavuus; phenotypes; genotypes; Breeds (animals); gender; aggressive behaviour; bites; productivity; tail biting; fattening pigs